Nutritional Status of Children 7–36 Months Old from Millet Consuming Communities of Masindi District, Western Uganda - Isingoma, Barugahara Evyline; Mbugua, Samuel Kuria; Karuri, Edward Gichohi (BMC nutrition, 2019)
Several national reports have indicated poor nutritional status among children from Western Uganda where millet porridge is a predominant complementary food. However, little is known about the nutritional status of 7–36 months old children from millet consuming communities of Western Uganda. A cross-sectional study was conducted in Bujenje County of Masindi District. A total of 636 children from 23 villages within Bwijanga and Budongo sub counties were randomly selected. Anthropometric measurements of children were taken. Data on demographic and socioeconomic characteristics of children’s households, their dietary practices and morbidity patterns was collected using a self-administered questionnaire. A statistical Package for the Social Sciences (SPSS) version 20 and Emergency Nutritional Assessment (ENA) Software Version 2010 were used for analysing data. The relationship between demographic and socioeconomic characteristics of households and children’s nutritional status was determined using Chi-square tests. Pearson’s correlation coefficient was used to determine the association between children’s nutritional status and the amount of millet porridge consumed. A p-value of < 0.05 indicated statistical significance. A proportion of 30.5% children were stunted, 11.6% underweight and 7.4% wasted. Underweight and wasting were significantly high in Budongo sub county at p = 0.044 and p = 0.005 respectively. Stunting and underweight were highest between 12 and 23 months at p = 0.005 and 0.020 respectively. Although millet porridges formed the bulk of children’s meals, they could only cater for < 60% of the recommended daily nutrient intake. Children with diarrhoea were 1.4 and 2 times likely to become stunted and underweight at p = 0.025 and 0.007 respectively. Feeding practices for children with diarrhoea were contrary to World Health Organisation’s recommendations in more than 50% of the studied children. There was a significant association between Height-for-Age Z scores, Weight-for-Height Z scores and the amount of millet porridge consumed by children (r = − 0.20, p < 0.001 and r = 0.14, p < 0.001 respectively). Results showed slightly higher percentages of stunted, underweight and wasted children compared to national figures. This was attributed to high incidences of diarrhoea and inadequate feeding practices especially for children 12–36 months old.
Keywords: Nutritional status, Millet consuming, 7–36 months, Western Uganda